Prognostic value of baseline LIPI, LDH and dNLR in ES-SCLC patients receiving immune checkpoint inhibitors: a systematic review and meta-analysis - Zhou, Chenyi; Hu, Quanman; Song, Xiaoru; Wang, Xiyin; Kong, Ran; Zhao, Fei; Wu, Boying; Chen, Shuaiyin; Jia, Bin (Frontiers in Immunology, 2025)
BackgroundExisting research presents conflicting findings on how baseline lung immune prognostic index (LIPI), lactate dehydrogenase (LDH), and derived neutrophil-to-lymphocyte ratio (dNLR) levels influence the prognosis of patients with extensive-stage small cell lung cancer (ES-SCLC) undergoing treatment with immune checkpoint inhibitors (ICIs). This meta-analysis aims to clarify their impact.MethodsA comprehensive search of published literature up to January 1, 2025 was conducted in PubMed, Web of Science, Cochrane Library, and Embase. The study evaluated the association between baseline LIPI, LDH, and dNLR levels and overall survival (OS) and progression-free survival (PFS) in ES-SCLC patients receiving ICIs. Subgroup analyses were performed based on relevant factors, and the study adhered to PRISMA 2020 guidelines.ResultsThis meta-analysis included 23 studies (LIPI: 10 studies/1,291 patients; LDH: 17 studies/1,768 patients; dNLR: 5 studies/324 patients). Elevated LIPI was significantly associated with poorer PFS (hazard ratio (HR) = 1.57, 95% confidence interval (95% CI) 1.20 - 2.06; I² = 59.0%, P = 0.013) and OS (HR = 1.76, 95% CI 1.26 - 2.45; I² = 64.2%, P < 0.001). Baseline LDH correlated with poorer OS (HR = 1.70, 95% CI 1.29 - 2.24; I² = 78.7%, P < 0.001), while elevated dNLR affected OS (HR = 2.05, 95% CI 1.02 - 4.12; I² = 86.31%, P < 0.001). Subgroup analysis showed that LIPI-PFS heterogeneity came from univariate and multivariate groupings. And LDH-OS heterogeneity was driven by country grouping.ConclusionIn ES-SCLC patients treated with ICIs, elevated baseline LIPI indicates reduced PFS and OS, while higher LDH and dNLR levels correlate with poorer OS. Monitoring these biomarkers can inform clinical decisions and enhance patient counseling.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251123579, identifier CRD420251123579.